Genealogy of Thought of the Founder of the Non-Aligned Movement in a Neorealist Perspective - Budiman, Bedi (IHSA Institute, 2024)
For newly independent countries emerging from colonial rule, the post-World War II situation (1945), which then continued with the Cold War (1947-1991), posed new threats to their sovereignty. Facing this dilemma, these countries sought to sustain themselves by organizing within the Non-Aligned Movement as a means to enhance their individual national capacities. The Non-Aligned Movement evolved into a third pole in the international system, successfully influencing the distribution of power on the global political stage. There are at least three major issues consistently advocated by the Non-Aligned Movement: decolonization, détente, and disarmament. This study examines how the founders of the Non-Aligned Movement conceptualized and acted in response to the anarchic world structure, the ideological contradictions between capitalism and communism, while still advocating for their respective national interests